Cystic Fibrosis Kidney Disease: 10 Tips for Clinicians - Nowakowski, Alexandra C. H. (Frontiers in Medicine, 2018)
Increased longevity in people with cystic fibrosis (CF) means that more people are surviving long enough to develop kidney complications. Nephrologists and their colleagues now face a steep learning curve as many of them encounter patients with CF related kidney disease for the first time. This article presents perspectives from a medical sociologist with CF on what renal health professionals should know about people with CF related kidney disease (CFKD). It outlines challenges that people with CFKD as they age, framing these struggles as opportunities for clinicians to help these unique patients achieve and maintain their best possible quality of life.